Eoin O'Duffy : a self-made hero - McGarry, Fearghal (Oxford University Press, 2005)
This biography explores themes as diverse as cultural nationalism, violence, sectarianism, militarism, and masculinity to shed new light on Irish republicanism and the politics of interwar European fascist movements.